ANALISIS TEORI BEHAVIORISME TERHADAP RENDAH NYA KEDISIPLINAN BELAJAR SISWA PASCA PANDEMI - Zahro', Silviana Khusniah; M. Mamduh Winangun (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The COVID-19 pandemic has significantly impacted the education sector, particularly in reducing students' learning discipline. The transition from face-to-face learning to online learning, followed by the return to offline learning in the post-pandemic period, has led to decreased motivation and weakened study habits among students. This article aims to analyze the phenomenon of low student learning discipline after the pandemic using the behaviorism learning theory perspective. The method used is a case study based on secondary data obtained from scientific journals, educational reports, and relevant literature. Behaviorism emphasizes that learning behavior is influenced by stimulus and response, strengthened through reinforcement. The results of the analysis indicate that low learning discipline is caused by a lack of positive reinforcement, weak environmental control, and changes in learning habits during online learning. Therefore, the proposed solutions include the application of positive reinforcement, the establishment of consistent learning habits, and strengthening the role of teachers and the learning environment in shaping disciplined behavior among students.